Selenium at the Neural Barriers: A Review - Solovyev, Nikolay; Drobyshev, Evgenii; Blume, Bastian; Michalke, Bernhard (Frontiers in Neuroscience, 2021)
Selenium (Se) is known to contribute to several vital physiological functions in mammals: antioxidant defense, fertility, thyroid hormone metabolism, and immune response. Growing evidence indicates the crucial role of Se and Se-containing selenoproteins in the brain and brain function. As for the other essential trace elements, dietary Se needs to reach effective concentrations in the central nervous system (CNS) to exert its functions. To do so, Se-species have to cross the blood-brain barrier (BBB) and/or blood-cerebrospinal fluid barrier (BCB) of the choroid plexus. The main interface between the general circulation of the body and the CNS is the BBB. Endothelial cells of brain capillaries forming the so-called tight junctions are the primary anatomic units of the BBB, mainly responsible for barrier function. The current review focuses on Se transport to the brain, primarily including selenoprotein P/low-density lipoprotein receptor-related protein 8 (LRP8, also known as apolipoprotein E receptor-2) dependent pathway, and supplementary transport routes of Se into the brain via low molecular weight Se-species. Additionally, the potential role of Se and selenoproteins in the BBB, BCB, and neurovascular unit is discussed. Finally, the perspectives regarding investigating the role of Se and selenoproteins in the gut-brain axis are outlined.